2009
DOI: 10.4049/jimmunol.0901264
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1-Mediated Impairment of the Intrinsic Apoptosis Pathway in Circulating Neutrophils from Critically Ill Patients Can Be Overcome by Fas Stimulation

Abstract: The systemic inflammatory response syndrome and subsequent organ failure are mainly driven by activated neutrophils with prolonged life span, which is believed to be due to apoptosis resistance. However, detailed underlying mechanisms leading to neutrophil apoptosis resistance are largely unknown, and possible therapeutic options to overcome this resistance do not exist. Here we report that activated neutrophils from severely injured patients exhibit cell death resistance due to impaired activation of the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 54 publications
10
62
0
Order By: Relevance
“…Exposure of neutrophils to TNF-related apoptosis-inducing ligand (TRAIL) resulted in enhanced apoptosis (Fig. 6F), consistent with previous studies showing the importance of extrinsic induced apoptotic pathways in neutrophil death (27,31,41). Inclusion of PAI-1 in the neutrophil cultures diminished the proapoptotic effects of TRAIL (Fig.…”
Section: Pai-1-dependent Activation Of Phosphatidylinositol 3-kinase supporting
confidence: 78%
“…Exposure of neutrophils to TNF-related apoptosis-inducing ligand (TRAIL) resulted in enhanced apoptosis (Fig. 6F), consistent with previous studies showing the importance of extrinsic induced apoptotic pathways in neutrophil death (27,31,41). Inclusion of PAI-1 in the neutrophil cultures diminished the proapoptotic effects of TRAIL (Fig.…”
Section: Pai-1-dependent Activation Of Phosphatidylinositol 3-kinase supporting
confidence: 78%
“…This prolonged neutrophil survival is associated with the accumulation of activated neutrophils contributing to an ongoing inflammation, and consecutive host tissue damage, with subsequent organ failure in critical ill patients. Profound inhibition of apoptosis has been already reported in neutrophils from patients with systemic inflammatory response syndrome (SIRS) (2,10), in sepsis (11)(12)(13)(14), as well as after burn injuries (15) and acute respiratory distress syndrome (8,16,17). These observations suggest that the resolution of the inflammatory response is highly dependent from the induction of neutrophil programmed cell death.…”
Section: Introductionmentioning
confidence: 62%
“…To measure the mitochondrial membrane potential, neutrophils were stained with the lipophilic dye 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazolocarbocyanine iodide (JC-1; Sigma Aldrich, Taufkirchen, Germany) as previously described (10). Then, cells immediately analyzed by flow cytometry.…”
Section: Detection Of Mitochondrial Membrane Depolarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuda et al (11) showed that cytokine-modulated inhibition of PMN apoptosis at a local site augments PMN functions and induces excessive inflammatory response. The anti-apoptotic B cell lymphoma-2 (Bcl-2) family members Bcl-X-linked, A1 and myeloid cell leukemia-1, have been demonstrated to inhibit PMN apoptosis and promote survival by antagonizing the pro-apoptotic proteins (35). However, Fas ligation or ligation of the tumor necrosis-related apoptosis-inducing ligand receptor on PMN may also trigger apoptosis (36)(37)(38).…”
mentioning
confidence: 99%